IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING DI MA DAR EL HIKMAH PEKANBARU - Harys Yusdar Rizki; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study uses descriptive method with a qualitative approach. The subject of this study was one GC teacher at school. Research data were obtained from open questionnaires and interviews. From the results of the study it can be concluded that the types of programs that have been prepared by GC teachers are annual, semester, and monthly programs. The program content includes orientation, information, placement and distribution services, content mastery, individual counseling, group guidance, group counseling, consultation, mediation, hand over cases, advocacy, and supporting activities in the form of implementation applications, data sets, case conferences, home visits, literature display. The implementation of the GC program in MA Dar El Hikmah Pekanbaru which has been carried out as much as 214 hours / semester or 8 hours / week then when compared with the total obligation of the workload of GC teachers regulated by Permendikbud No 111 of 2014, as much as 24 hours / week so that program implementation can be concluded GC has been achieved in MA Dar El Hikmah Pekanbaru as much as 33% of the total workload obligations of GC teachers.Key Words: Guidance and Counseling Program, Implementation